The cytoprotective effects of dihydromyricetin and associated metabolic pathway changes on deoxynivalenol treated IPEC-J2 cells. (15th February 2021) - Long, Hongrong; Xin, Zhongquan; Zhang, Fan; Zhai, Zhenya; Ni, Xiaojun; Chen, Jialuo; Yang, Kang; Liao, Pinfeng; Zhang, Limeng; Xiao, Zaili; Sindaye, Daniel; Deng, Baichuan
Highlights: DHM effectively restrained the cytotoxicity of DON in IPEC-J2 cells. DHM relieves cell viability reduction, inflammatory response and oxidative stress reaction induced by DON. DHM may weaken the toxic effect of DON by stabilizing glutamate metabolism, arachidonic metabolism and histidine metabolism. Abstract: In this study, we investigated the cytoprotective effects of dihydromyricetin (DHM) against deoxynivalenol (DON)-induced toxicity and accompanied metabolic pathway changes in porcine jejunum epithelial cells (IPEC-J2). The cells were incubated in 250 ng/ml DON cotreated with 40 µM DHM, followed by toxicity analysis, oxidative stress reaction analysis, inflammatory response analysis and metabolomic analysis. The results showed that DHM significantly increased the cell viability ( P  < 0.01), the intracellular GSH level ( P  < 0.01) and decreased the intracellular ROS level ( P  < 0.01), the secretion of TNF-α, IL-8 ( P  < 0.01) and the apoptotic cell percentages ( P  < 0.01) in IPEC-J2 cells compared to that in the DON group. Metabolomic analysis revealed that DHM recovered the disorder of metabolic pathways such as glutamate metabolism, arachidonic metabolism and histidine metabolism caused by DON. In summary, DHM alleviated cell injury induced by DON and it is possibly through its antioxidant activity, anti-inflammatory activity or ability to regulate metabolic pathways.